Chemoenzymatic total synthesis of cryptocaryalactone natural products. Issue 2 (10th January 2018) - Reddy, Yarram Narasimha; Kumari, Tenkayala Navya; Thota, Pradeepkumar; Jyothi, Perla; Gupta, Ajay Kumar
Graphical abstract: Highlights: New chemoenzymatic route for the synthesis of cryptocaryalactones natural products. Novozyme-435 hydrolysis provided optically pure enantiomers with high ee values. Enantiomer converted to natural products using Wittig-reaction and lactonization. Abstract: A new chemoenzymatic route for the preparation of cryptocaryalactones natural products using a kinetic resolution process as the key step is described. Novozyme-435 catalyzed hydrolysis of the prochiral (±)-monoester7 afforded the precursors of cryptocaryalactones with high enantiomeric excess and excellent yields. The compounds (4 S, 6 S )-7 and (4 R, 6 R )-7 were converted to (+)-(6 R, 2′ S )-cryptocaryalactone (1 ) and (−)-(6 S, 2′ R )-cryptocaryalactone (2 ), respectively by employing Wittig-olefination, lactonization and acylation reactions.